Market Reactions to Football Match Results: The Effect of Venues and Competition Types - Dwi Apredianto, Krismon; Rambu Atahau, Apriani Dorkas; Huruta, Andrian Dolfriandra (The European Journal of Applied Economics, 2021)
This study seeks to investigate the stock market reaction to football match results in different venues and competition types, especially for three major football clubs: Manchester United, Juventus FC, and Borussia Dortmund. We use a parametric paired sample t-test. The findings show that investors take not only match results but also venues and competition types into consideration when making investment decisions. This study indicates the stock markets of football clubs are semi-strong efficient markets. Different market reaction on match results for each football club studied implies the importance of understanding the specific characteristics of those clubs in making investment decisions. The findings suggest the football club investors need to consider their clubs’ competitive performance in different venues and competition types when making portfolio investment decisions. This study complemented the previous assumption on the importance of venues, and competition types match results in making investment decisions.